Global Transformations and Russia: the Sources of Confrontation and Prospects for Cooperation - Dmitry Evstafiev (Международная аналитика, 2018)
Increased and diversified tensions in Russian-Western relations and first Russian-American relations are not only а result of propaganda pressure. They also reflex a number of conflicting realities of the contemporary system of international political and economic relations that involve Russia as an important player. The role of Russia is especially noticeable now that the process of development of the architecture of a new global system is underway. Hostile or confrontational position of Russia could be a major risk as well as a factor that can change the strategic context of the global competition. The emerging system looks much different from the one that formed the basis on which the world developed during the last 30 years. In that environment a potential hostile position of Russia is regarded as a major risk. But the active involvement of Russia into most important recent global economic and political developments prevents the situation of surpassing the limits of the «non-zero sum game».